The Correlation between TNF-α Serum Level and Andropause with Quality of Life on Elderly - Trisna Yuliharti Tersinanda; RA Tuty Kuswardhani; Wimpie I Pangkahila (GLOBAL HEALTH SCIENCE GROUP, 2020)
As the population of elderly increases, the number of andropause also increases. Andropause is characterized by the decrease of testosteron level which is accompanied by hypogonadism symptoms. Many studies mentioned that decreased testosterone level will contribute to inflammation state, one of the cytokine is TNF-α, which then lead to many chronic inflammation disorders and influence the quality of life. Understanding the significant correlation between androgen and inflammation allows accurate consideration making in using androgen replacement therapy, therefore the quality of life will be improved significantly.This research was an analytical cross-sectional study. Subjects were recruited through random sampling at Denpasar in 2019. TNF-α serum level was measured by human immunoassay method. Andropause was measured by ADAM questionnaire and confirmed by total decreased testosterone serum level. Quality of life was measured by WHOQOL-BREF questionnaire which was then continued by bivariate and multivariate analysis to control the confounding variables. It was considered statistically significant if P value is more than 0.05. There were 60 elderly involved as research subjects consisting of 43 andropause cases and 17 non andropause cases. There was significant correlation between TNF-α serum and quality of life. This study also found that there was significant difference in quality of life between andropause and non andropause group. This study shows that there was significant correlation between TNF-α serum level and andropause with quality of life in elderly.